2018
DOI: 10.5935/abc.20180181
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation Catheter Ablation Outcome Depends on Pulmonary Veins Anatomy

Abstract: BackgroundPulmonary veins (PV) are often the trigger to atrial fibrillation (AF). Occasionally, left PVs converge on a common trunk (LCT) providing a simpler structure for catheter ablation.ObjectiveTo compare the clinical characteristics and outcomes of ablation in paroxysmal atrial fibrillation (PAF) of patients with or without LCT.MethodsCase-control study of patients undergoing first-ever catheter ablation procedure for drug refractory PAF. The information was taken from patients' records by means of a dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
(20 reference statements)
0
9
1
2
Order By: Relevance
“…Hunter et al analyzed the relationship between PVs anatomy and outcomes of AF ablation in 255 patients (an LCPV in 15% patients) and found that an LCPV was associated with a 12.8% absolute decrease in first procedure success. However, the result was in contrast to more recent studies, which reported that an LCPV was an independent predictor of AF freedom after index ablation . There were also several studies reporting no association between an LCPV and outcomes of initial AF ablation .…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Hunter et al analyzed the relationship between PVs anatomy and outcomes of AF ablation in 255 patients (an LCPV in 15% patients) and found that an LCPV was associated with a 12.8% absolute decrease in first procedure success. However, the result was in contrast to more recent studies, which reported that an LCPV was an independent predictor of AF freedom after index ablation . There were also several studies reporting no association between an LCPV and outcomes of initial AF ablation .…”
Section: Discussioncontrasting
confidence: 66%
“…Second, as mentioned above, no united definition of the LCPV exists. In the current study, we applied the definition described by cardiac pathologist Cabrera et al The results should be explained with caution when another definition is applied. Third, force contact catheter technology was seldom applied in our study, which might provide underlying mechanisms of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sohns y colaboradores valoraron la anatomía de las VP utilizando TC de 64 cortes y observaron que una anatomía atípica, diferente a cuatro venas, cada una con su propio ostium, es un fuerte predictor de recurrencia, siendo la variante tronco común izquierdo la que asocia un riesgo mayor (24) . Contrariamente, Odozynski y colaboradores valoraron de forma retrospectiva la anatomía de las VP de pacientes que recibieron ablación de FA paroxística refractaria a fármacos antiarrítmicos y observaron que la presencia de un tronco común izquierdo se relaciona con menos recurrencia (25) . Huang y colaboradores, en un estudio prospectivo utilizando crioablación, demostraron que las variantes en la anatomía de las VP no son factores predictores de éxito a largo plazo (26) .…”
Section: Anatomía De Las Venas Pulmonaresunclassified